Pathways to psychiatric care for mental disorders: a retrospective study of patients seeking mental health services at a public psychiatric facility in Ghana. Issue 1 (December 2016) - Ibrahim, Abdallah; Hor, Sidua; Bahar, Ozge; Dwomoh, Duah; McKay, Mary; Esena, Reuben; Agyepong, Irene
Abstract Background The process to seek for care by patients who experience episodes of mental disorders may determine how and where they receive the needed treatment. This study aimed to understand the pathways that people with mental disorders traversed for psychiatric services, particularly where these individuals will first seek treatment and the factors that influence such pathways to mental health care. Methods A cross-sectional study conducted at Pantang psychiatric hospital in Accra, Ghana involving 107 patients of ages 18 and older and their family members. The study adapted the World Health Organization's (WHO) pathway encounter form to collect information about patients' pathway contacts for psychiatric care. Chi Square test was done to determine patients' first point of contact and any association between the independent variables (clinical diagnosis and socio-demographic factors) and first pathway contact. Multiple regression analyses were also done to estimate the odds of patients' first pathway contact. Results Overall, nearly 48 % of patients initially contacted non-psychiatric treatment centers (faith-based, traditional healers and general medical practitioners) as their first point of contact for treatment of mental disorders. A little more than half of the patients went directly to the formal public psychiatric facility as their first point of contact for care of their mental disorders. Patients' occupation was significantly associated with their first point of contact for psychiatric care (χ 2  = 6.91; p < 0.033). Those with secondary education were less likely to initially seek care from the formal public psychiatric hospital compared to those with no formal education (uOR = 0.86; 95 % CI 0.18–4.08). Conclusion Patients used different pathways to seek psychiatric care, namely direct pathway to a psychiatric hospital or through transition from informal non-psychiatric service providers. Since nearly half of patients do not initially seek mental health care directly at the formal psychiatric facility, it is important for the government of Ghana to increase funding to the mental health authorities in Ghana as a matter of priority so that more individuals can be identified and integrated into mainstream psychiatric treatment and general health facilities where there are trained Community Mental Health Officers (CMHO) and Clinical Psychiatric Officers (CPO) to provide early intervention and treatment.